PERBEDAAN ANTARA PENGARUH INSTRUKSI LANGSUNG DAN PENGAJARAN UNTUK MEMAHAMI PENDEKATAN HASIL BOLABASKET YANG DITINJAU DARI MINAT SISWA - Setiaji, Joko (Universitas Negeri Semarang, 2017)
The aim of this study is to know: (1) the difference between effect of DI and TGfU. (2) The difference in the playing basketball result among students interest. (3) The effect of interaction between learning approaches and interest in basketball outcomes. Data collection used playing basketball with a test of basketball. Data retrieval is conducted with GPAI. Data collection of students? interest used questionnaires. The data analysis technique in this study used two-way variance analysis and Newman Keuls range test, at 5% significance level. The conclusion: (1) There is a significant difference between effect of DI and TGfU. (2) There is a significant difference in basketball outcomes between students interest. (3) There is a significant interaction effect between learning approach and interest in basketball game.